The need for pre trial discovery in criminal cases in Malaysia / Rozana Shamsuddin - Shamsuddin, Rozana (Faculty of Law, 1987)
It is obvious that a case, whether it be a civil or criminal depends on evidence. Part of this evidence may be oral and part of it documentary. In a civil case, this evidence consisting perhaps of agreements, deeds, correspondence and even tape recordings. The oral evidence must come from witnesses who will testify in Court but the documentary evidence will be derived’ from the documents themselves. It will be of great assistance if before the trial, the parties make known ie. discover to each other, what documents they have, are allowed to inspect the other party‘s documents intended to be used at the trial and to facilitate the proof of these documents by agreeing on them. Inspection of documents will prevent the other party from being taken by surprise and will shorten the time of the hearing and therefore save costs. The rules of evidence require, in the ordinary way, that a document to become evidence must be proved by calling its maker. Agreement on documents will dispense with this necessity of proof and will also ne time and lower the costs of the trial.